Adjuvant composite cold atmospheric plasma therapy increases antitumoral effect of doxorubicin hydrochloride - Kniazeva, Volha; Tzerkovsky, Dzmitry; Baysal, Ömür; Kornev, Alexander; Roslyakov, Evgeny; Kostevitch, Serhei (Frontiers in Oncology, 2023)
Introduction Cancer is a global health concern, with a significant impact on mortality rates. Despite advancements in targeted antitumor drugs, the development of new therapies remains challenging due to high costs and tumor resistance. The exploration of novel treatment approaches, such as combined chemotherapy, holds promise for improving the effectiveness of existing antitumor agents. Cold atmospheric plasma has demonstrated antineoplastic effects in preclinical studies, but its potential in combination with specific ions for lymphosarcoma treatment has not been investigated. Methods An in vivo study was conducted using a Pliss lymphosarcoma rat model to evaluate the antitumor effects of composite cold plasma and controlled ionic therapy. Groups of rats were exposed to composite cold plasma for 3, 7, and 14 days, while the control group received no treatment. Additionally, a combination of chemotherapy with cold plasma therapy was assessed, with doxorubicin hydrochloride administered at a dosage of 5 mg/kg. PERENIO IONIC SHIELD™ emitted a controlled ionic formula during the treatment period. Results The in vivo study demonstrated tumor growth inhibition in groups exposed to composite cold plasma for 3, 7, and 14 days compared to the control group. Furthermore, combining chemotherapy with cold plasma therapy resulted in a threefold reduction in tumor volume. The most significant antitumor effects were observed when doxorubicin hydrochloride at a dosage of 5 mg/kg was combined with 14 days of PERENIO IONIC SHIELD™ ionic therapy. Discussion The use of composite cold plasma therapy, in conjunction with a controlled ionic formula emitted by PERENIO IONIC SHIELD™, in the complex treatment of lymphosarcoma in rats showed promising antitumor effects. The combination therapy, particularly when combined with doxorubicin hydrochloride, demonstrated enhanced efficacy. These findings suggest the potential for utilizing cold atmospheric plasma and controlled ions as an adjunctive treatment approach in lymphosarcoma therapy. Further research is warranted to explore the mechanisms underlying these effects and to evaluate the safety and efficacy in human clinical trials.